2011
DOI: 10.1111/j.1365-2702.2011.03905.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ perceptions and attitudes towards computerisation in a private hospital

Abstract: The nurse managers should promote an institutional culture to motivate staff towards positive acceptance of innovation. An effective collaboration with the information technology team would enhance a more efficient exchange of information to understand the complex factors of IT implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 24 publications
(34 reference statements)
6
38
0
2
Order By: Relevance
“…Similar findings were also reported by Ash JS et al and Axford RL et al 9,10 The findings of the present study are in conformity with the study done by Chow SK et al as the present study showed that more than 50% of nurse administrators found hospital information system to improve patient safety and satisfaction. 11 The study findings by Chow SK also showed similar results where the nurses have also pointed that hospital system was useful and enhanced patient safety.…”
Section: Positive Perceptionsupporting
confidence: 70%
“…Similar findings were also reported by Ash JS et al and Axford RL et al 9,10 The findings of the present study are in conformity with the study done by Chow SK et al as the present study showed that more than 50% of nurse administrators found hospital information system to improve patient safety and satisfaction. 11 The study findings by Chow SK also showed similar results where the nurses have also pointed that hospital system was useful and enhanced patient safety.…”
Section: Positive Perceptionsupporting
confidence: 70%
“…However, successful implementation of the computer and computer systems depends mainly on the nurses'/in-service training nurses' attitudes its use and acceptance (Oroviogoicoechea et al, 2010;Chow et al, 2011). So, user attitudes are viewed as the components influencing the user technology adoption level and have been found critical to successful computer and computer system implementation (McLane, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Besides producing, processing, storing, distributing and using information, the computers increase the level of learning by simultaneously addressing several senses, create permanent learning, save from time, place and learning speed and support life-long learning. With such attributes, the computers support efficient fulfillment of the roles, functions and responsibilities of the nurses/in-service training nurses, increase the quality of health care and enhance quality and efficiency of nursing practice (McNeil et al, 2003;Jiang et al, 2004;Lee, 2008;ANCC, 2010;Chow et al, 2011;Kaya, 2011;Lın et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Chow i suradnici navode da otkrića ove studije mogu dati smjernice upraviteljima medicinskih sestara i programerima u njihovu shvaćanju složenih čimbenika primjene informacijske tehnologije te im pomoći razviti sustave prilagođene korisnicima koji odgovaraju potrebama korisnika [18].…”
Section: Metode I Ispitanici / Methods and Subjectsunclassified